Parenting Children with Mental Retardation in the RSUD DR. SOETOMO - Rahmadhanti, Diah Caesaria Garindra; Febriyana, Nining; Suryawan, Ahmad; Setiawati, Yunias (Universitas Airlangga, 2019)
Introduction: Parenting applied by parents in caring for children with mental retardation, plays a role in shaping the child's character. However, often parents do not understand the condition of their children who suffer from mental retardation. This study aims to determine the general picture of parenting parents of children with mental retardation.Method: This study was a descriptive study with a cross sectional approach. Data was collected by means of the Child Care Parenting Questionnaire (KPAA) instrument. Determination of the number of sample subjects is random sampling, with a minimum number of 17 samples. Criteria for inclusion of subjects were parents of mental retarded pediatric patients who had or were undergoing therapy and were analyzed using univariate analysis, this analysis was used to determine the frequency distribution and explain or describe the characteristics of each study variable.Results: Based on data analysis conducted, from 20 respondents, obtained results of parenting in children with permissive mental retardation as much as 55% (11 people), 30% authoritarian form (6 people), and 15% authoritative form person).Conclusion: Most of the respondents have permissive parenting (55%) with the age category of parents most of them are early adulthood (75%), and the level of parental education is mostly junior high school (40%), and children with mental retardation are mostly mild mental retardation category (65%). From the results of the study it is expected that parents who have children with mental retardation, better understand their children by not always giving full freedom, but also not always demanding, so they can provide the best parenting that has been adjusted by parents to the child's condition in order to achieve a quality of life optimal.